A multicenter examination and strategic revisions of the Yale Global Tic Severity Scale. (8th May 2018) - McGuire, Joseph F.; Piacentini, John; Storch, Eric A.; Murphy, Tanya K.; Ricketts, Emily J.; Woods, Douglas W.; Walkup, John W.; Peterson, Alan L.; Wilhelm, Sabine; Lewin, Adam B.; McCracken, James T.; Leckman, James F.; et al.
Abstract : Objective: To examine the internal consistency and distribution of the Yale Global Tic Severity Scale (YGTSS) scores to inform modification of the measure. Methods: This cross-sectional study included 617 participants with a tic disorder (516 children and 101 adults), who completed an age-appropriate diagnostic interview and the YGTSS to evaluate tic symptom severity. The distributions of scores on YGTSS dimensions were evaluated for normality and skewness. For dimensions that were skewed across motor and phonic tics, a modified Delphi consensus process was used to revise selected anchor points. Results: Children and adults had similar clinical characteristics, including tic symptom severity. All participants were examined together. Strong internal consistency was identified for the YGTSS Motor Tic score (α = 0.80), YGTSS Phonic Tic score (α = 0.87), and YGTSS Total Tic score (α = 0.82). The YGTSS Total Tic and Impairment scores exhibited relatively normal distributions. Several subscales and individual item scales departed from a normal distribution. Higher scores were more often used on the Motor Tic Number, Frequency, and Intensity dimensions and the Phonic Tic Frequency dimension. By contrast, lower scores were more often used on Motor Tic Complexity and Interference, and Phonic Tic Number, Intensity, Complexity, and Interference. Conclusions: The YGTSS exhibits good internal consistency across children and adults. The parallel findings across Motor and Phonic Frequency, Complexity, and Interference dimensions prompted minor revisions to the anchor point description to promote use of the full range of scores in each dimension. Specific minor revisions to the YGTSS Phonic Tic Symptom Checklist were also proposed.